The Values of Mentoring Entrepreneurs - Viktor, Kéri; Zoltán, Horváth; Hegedűs, Szilárd (Acta Carolus Robertus, 2024)
The National Entrepreneur Mentoring Program has a significant positive impact on the development of small and medium-sized enterprises (SMEs), especially in the case of enterprises run by women. The central role of mentoring lies in the transfer of knowledge based on practical experience and direct exchange of information, which promotes the growth of businesses. During the selection of mentors, the dominance of the professional scientific sector can be observed, while the geographical location has less influence on the choice. Women participating in the program are overrepresented, which indicates that the support provided by mentoring is particularly important for them. Mentors with higher qualifications and more experience are preferred, especially for women-owned businesses. The results show that mentoring plays a key role in the success and sustainable growth of businesses, especially in the case of full-time, younger, highly educated female entrepreneurs who are fully committed to developing their businesses.
Keywords: female entrepreneurship; mentoring; business development; business mentoring